Language Representation of the Concept of “Wealth” and “Poverty” in Kazakh, Chinese and English - Mukanova, D.; Mazhitayeva, Sh.; Aubakir, S.; Kitibaeva, A.; Buketova, N. (XLinguae, 2025)
In the conceptual realm of any language, there are a number of the most significant concepts; the majority are universal for all languages; however, their value component may differ due to some value ideas of one or another ethnocultural community. The purpose of the study is to identify the distinctive and common features that make up the concepts of “wealth” and “poverty” in Kazakh, Chinese, and English. To achieve this goal, general scientific methods were used, as well as special research methods, such as experiments, modeling, and forecasting. The main result of the study was the conclusion that the linguistic representation of the concept of “wealth” and “poverty” in the Kazakh, Chinese, and English languages in the collective consciousness of native speakers of this language is represented by lexical units with a variety of semantics, which is due to the cultural, historical and spiritual traditions of a particular people. Results confirm that the components of the concept of “wealth” and “poverty” in Kazakh, Chinese, and English are interconnected, mobile, and dynamic, which change with the evolution of the social world. The study also noted that the concept itself contains not only a linguistic but also a cultural and philosophical aspect. The practical value of the results lies in the possibility of their use in further scientific developments in comparative philology and psycholinguistics.
Keywords: associative reaction; cognitive linguistics; cognitive stereotypes; intercultural communication; language picture; linguistic culture; motivating feature